EFEKTIVITAS PETIDIN 25 MG INTRAVENA UNTUK MENCEGAH MENGGIGIL PASCA ANESTESI UMUM - Kresnoadi, Erwin; Rahman, Hadian; Affarah, Wahyu Sulistya (Faculty of Medicine Universitas Mataram, 2013)
Background : Post anesthesia complication scan be caused by various factors, shivering is quite frequently encountered complications during recovering time. Risks that may happen is increasing of metabolism and make post operative pain worst. This study proves petidine can be used as an alternative to prevent shivering after general anesthesia. Methods : This research includes phase II clinical trials, the sample selection by Quota Sampling of patients are being prepared for elective surgery with general anesthesia, aged 20-40 years, ASA I-II, all patients who meet the criteria for inclusion in the sample until the required number met, willing to volunteer. Randomization was done at the end of the operation. Patients were divided into two groups, Pand S.Severity of shivering were recorded and assessed. Results : Characteristics of patients five minutes before induction did not significant differences. Measurement of systolic blood pressure and heart rate immediately after extubation showed significant differences. Duration of shivering in saline group occurredin almost the same when compared with the treatment group, because after the shivering, the patient is given immediate intervention of meperidine of 25mg for the treatment of shivering occurred, especially given to people who experience shivering with2nd, 3rd, or 4th degree. For patients shivered first degree was given meperidine administration intervention. Duration of shivering in the control group took place in almost the same time. Conclusion : Pethidine had a good effectiveness in preventing the occurrence of shivering after general anesthesia. Keywords: Pethidine, shivering after general anesthesia.